The use of the Clock Drawing Test in bipolar disorder with or without dementia of Alzheimer’s type - Ivan Aprahamian; Marcia Radanovic; Paula Villela Nunes; Rodolfo Braga Ladeira; Orestes Vicente Forlenza (Arquivos de Neuro-Psiquiatria)
There is limited data regarding the cognitive profile from screening tests of older adults with bipolar disorder (BD) with dementia. Objective To investigate the Clock Drawing Test (CDT) among older adults with BD with and without Alzheimer’s disease (AD). Method 209 older adults (79 with BD without dementia and 70 controls; 60 with AD, being 27 with BD) were included to evaluate the performance of three CDT scoring scales, beyond the Mini-Mental State Examination (MMSE) and verbal fluency (VFT). Results Patients with BD without dementia presented with lower scores in MMSE, VF and one CDT scoring scale than controls. Patients with BD and AD presented with lower scores in VF and CDT scoring scales than patients with only AD. All CDT scales presented similar sensitivity and specificity for BD and non-BD groups. Conclusion Elderly subjects with BD showed greater impairment in CDT in both groups of normal cognition and AD.